Comparison of lesion detection and quantitation of tracer uptake between PET from a simultaneously acquiring whole-body PET/MR hybrid scanner and PET from PET/CT - Wiesmüller, Marco; Quick, Harald H.; Navalpakkam, Bharath; Lell, Michael; Uder, Michael; Ritt, Philipp; Schmidt, Daniela; Beck, Michael; Kuwert, Torsten; von Gall, Carl (European Journal of Nuclear Medicine and Molecular Imaging, 2013)
Purpose PET/MR hybrid scanners have recently been introduced, but not yet validated. The aim of this study was to compare the PET components of a PET/CT hybrid system and of a simultaneous whole-body PET/MR hybrid system with regard to reproducibility of lesion detection and quantitation of tracer uptake. Methods A total of 46 patients underwent a whole-body PET/CT scan 1 h after injection and an average of 88 min later a second scan using a hybrid PET/MR system. The radioactive tracers used were 18F-deoxyglucose (FDG), 18F-ethylcholine (FEC) and 68Ga-DOTATATE (Ga-DOTATATE). The PET images from PET/CT (PETCT) and from PET/MR (PETMR) were analysed for tracer-positive lesions. Regional tracer uptake in these foci was quantified using volumes of interest, and maximal and average standardized uptake values (SUVmax and SUVavg, respectively) were calculated. Results Of the 46 patients, 43 were eligible for comparison and statistical analysis. All lesions except one identified by PETCT were identified by PETMR (99.2 %). In 38 patients (88.4 %), the same number of foci were identified by PETCT and by PETMR. In four patients, more lesions were identified by PETMR than by PETCT, in one patient PETCT revealed an additional focus compared to PETMR. The mean SUVmax and SUVavg of all lesions determined by PETMR were by 21 % and 11 % lower, respectively, than the values determined by PETCT (p < 0.05), and a strong correlation between these variables was identified (Spearman rho 0.835; p < 0.01). Conclusion PET/MR showed equivalent performance in terms of qualitative lesion detection to PET/CT. The differences demonstrated in quantitation of tracer uptake between PETCT and PETMR were minor, but statistically significant. Nevertheless, a more detailed study of the quantitative accuracy of PETMR and the factors governing it is needed to ultimately assess its accuracy in measuring tissue tracer concentrations.

Discrimination between Inflammatory and Fibrotic Activity in Crohn's Disease-Associated Ileal-Colonic Anastomotic Strictures by Combined Ga-68-FAPI-46 and F-18-FDG-PET/CT Imaging - Beck, Michael; Kuwert, Torsten; Atzinger, Armin; Gerner, Maximilian; Hartmann, Arndt; Saake, Marc; Uder, Michael; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2024)
Introduction: The development of an intestinal stricture in patients with Crohn s disease represents an important and frequent complication, reflecting the progressive nature of the disease. Depending on the inflammatory and fibrotic composition of the stricture, intensified medical therapy, interventional endoscopy, or surgical intervention is required. However, currently available diagnostic approaches can only assess the level of inflammation, but not the degree of fibrosis, limiting rational therapeutic management of Crohn s disease patients. Recently, prolyl endopeptidase fibroblast activating protein (FAP) has been functionally implicated in fibrotic tissue remodelling, indicating it as a promising target for detection of sites of fibrotic tissue remodelling. Thus, intestinal fibrosis might be visualized using Gallium-68 labelled inhibitors of FAP (FAPI). While F-18-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT is a standard diagnostic tool for visualizing inflammatory processes, we combined Ga- 68-FAPI-46-PET/CT and F-18-FDG-PET/CT to differentiate predominantly fibrotic or inflammatory areas in Crohn s disease patients with ileo-colonic strictures. Methods: In our study, we analysed three Crohn s disease patients with anastomotic ileo-colonic strictures who underwent both dynamic Ga-68-FAPI-46-PET/CT and static F-18-FDG-PET/CT imaging to assess the level of visualized fibrotic areas within the stricture and differentiate it from inflammatory ones. PET images were analysed both visually and quantitatively. Furthermore, conventional MR enterography and endoscopy were performed in parallel to correlate observed findings. Two of the included patients underwent surgery and the histological specimen were analysed for the level of inflammation and fibrosis, which results were similarly compared to the findings of the PET imaging procedures. Results: Different uptake patterns of Ga-68- FAPI-46 could be observed in the anastomotic ileo-colonic strictures of the examined Crohn s disease patients, respectively. Immunohistochemical analyses demonstrated that there was a correlation between the level of Ga-68- FAPI-46 uptake and severity of fibrosis, while FDG uptake correlated with the inflammatory activity in the analysed strictures. Discussion: The combination with F-18-FDGPET/CT represents a promising imaging modality to distinguish inflammation from fibrosis and guide subsequent therapy in stricturing Crohn s disease patients, warranting further studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Crohn s disease; FAPI-PET/CT; Fibrosis; Ga-68-FAPI-46; Strictures

Individualisierte Präzisionsmedizin - Wullich, Bernd; Taubert, Helge; Goebell, Peter; Kuwert, Torsten; Beck, Michael; Schott, Christian; Baur, Andreas; Eckstein, Markus; Wach, Sven (Die Urologie, 2023)
Spectacular advances have been made in personalized medicine , which has rapidly revolutionized our traditional understanding of disease diagnosis and treatment. Molecular testing of tissue and liquid samples using next generation sequencing has developed into a key technology in this scenario. It can be used for both the determination of biomarkers for diagnostic, prognostic and predictive purposes, as well as the possible improvement of treatment outcome through the use of targeted therapies and the avoidance of therapies in the event of special resistance situations. In addition to drugs that have already been approved, which among other things intervene in cellular DNA repair, many new drugs have been developed and are in clinical testing. Furthermore, new possibilities in molecular imaging have dramatically expanded our understanding of tumor spread and created new approaches for targeted therapies.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Biomarkers; Cancer; Liquid biopsy; Next generation sequencing; PSMA

Liver-FDG-uptake augments early PET/CT prognostic value for CD19-targeted CAR-T cell therapy in diffuse large B cell lymphoma - Beck, Michael; Blumenberg, Viktoria; Bücklein, Veit L.; Bundschuh, Ralph A.; Harrer, Dennis C.; Hirschbühl, Klaus; Jung, Johannes; Kunz, Wolfgang G.; Menhart, Karin; Winkelmann, Michael; Yakushev, Igor; Illert, Anna Lena; et al. (EJNMMI Research, 2025)
Background: Despite revolutionary efficacy of CD19-CAR-T cell therapy (CAR-T) in aggressive B cell lymphoma, many patients still relapse mostly early. In early failure, distinct drugs support CAR-T which makes reliable and early prediction of imminent relapse/refractoriness critical. A complete metabolic remission (CR) on Fluor-18-Deoxyglucose (FDG) Positron-Emission-Computed Tomography (PET) 30 days after CAR-T (PET30) strongly predicts progression-free survival (PFS), but still fails in a relevant proportion of patients. We aimed to identify additional routine parameters in PET evaluation to enhance CAR-T response prediction. Results: Thirty patients with aggressive B cell lymphoma treated with CAR-T were retrospectively analyzed. Pre-CAR-T, LDH was the strongest PFS-predictor also by multivariate analysis. Post-CAR-T, 10 out of 14 patients (71.4%) with PET30-CR remained in disease remission, while 12 out of 16 patients (75%) with incomplete metabolic remission (PET30-nCR) relapsed after CAR-T. 28.6% of patients with PET30-CR ultimately progressed. Change of liver FDG-uptake from baseline to day30 (Delta-Liver-SUVmean) was identified as an independent biomarker for response. PET30-nCR and a decrease of Delta-Liver-SUVmean were associated with a high risk of tumor progression (HR 4.79 and 3.99, respectively). The combination of PET30 and Delta-Liver-SUVmean identified patients at very low, at intermediate and at very high risk of relapse (PFS not reached, 7.5 months, 1.5 months, respectively). Conclusion: Additionally to PET30 metabolic remission, longitudinal metabolic changes in Delta-Liver-SUVmean predicted CAR-T efficiency. Our results may guide early intervention studies aiming to enhance CAR-T particularly in the very high-risk patients.
CRIS-Team Scopus Importer:2025-04-01
Keywords: CAR T cell therapy; DLBCL; FDG PET; Liver-SUV

Multimodal imaging of bone metastases: From preclinical to clinical applications - Ellmann, Stephan; Beck, Michael; Kuwert, Torsten; Uder, Michael; Bäuerle, Tobias (Journal of Orthopaedic Translation, 2015)
Metastases to the skeletal system are commonly observed in cancer patients, highly affecting the patients' quality of life. Imaging plays a major role in detection, follow-up, and molecular characterisation of metastatic disease. Thus, imaging techniques have been optimised and combined in a multimodal and multiparametric manner for assessment of complementary aspects in osseous metastases. This review summarises both application of the most relevant imaging techniques for bone metastasis in preclinical models and the clinical setting.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bone metastases; Computed tomography; Magnetic resonance imaging; Multimodal imaging; Positron-emission tomography; Translational research

Thyroglossal duct cyst carcinomas — a retrospective study and systematic review of the literature - Thimsen, Vivian; Müller, Sarina Katrin; Agaimy, Abbas; Agaimy, Abbas; Mantsopoulos, Konstantinos; Beck, Michael; Koch, Michael; Iro, Heinrich; Sievert, Matti (Virchows Archiv, 2025)
The aim of this study was to analyze thyroglossal duct cyst carcinoma (TDCC) in a single-center retrospective analysis, supplemented by a systematic literature review to inform treatment approaches. Patient records from a tertiary referral center were analyzed for individuals diagnosed with TDCC between 2002 and 2023. A systematic review followed the PRISMA guidelines, encompassing studies from Medline and PubMed. Patient data, including demographics, imaging results, and histological findings were extracted. The primary outcome assessed was tumor-free and recurrence-free survival, while additional variables included treatment regimens and follow-up data. The analysis identified a total of 484 TDCC cases, confirming papillary thyroid carcinoma (PTC) as the predominant type (94.2%), with synchronous thyroid gland carcinomas observed in 34.6%. The age range was 8 to 76 with median age of 40 years. Women were affected in 62%, men in 36%. The recurrence rate was 7.4%, with distant metastases observed in 1% of cases. The overall survival rate was 99.1%, regardless of the treatment regimen. Although rare, TDCC predominantly presents as PTC, with a favorable prognosis. Sistrunk’s procedure remains the primary surgical approach, but optimal management regarding therapies such as total thyroidectomy, neck dissection, or radioiodine ablation requires careful evaluation of risk factors like rare tumor types, suspicious lymph nodes, thyroid nodules, age, radiation exposure, and molecular patterns. Emphasizing more individualized treatment strategies, we propose an algorithm that can help to reduce invasiveness and overtreatment risks in selected cases.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Carcinoma; Papillary; Thyroglossal duct cyst; Treatment algorithm

Zufallsbefund Schilddrüsenknoten: Stellenwert der Sonographie und Szintigraphie in der Primärdiagnostik - Richter, Daniel; Beck, Michael; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael; Sievert, Matti (HNO, 2024)
Due to the widespread use of high-resolution sonography, numerous thyroid nodules are diagnosed, often as incidental findings. The challenge lies in evaluating various criteria such as size, shape, and echogenicity to assess the nodules’ malignancy risk. Risk stratification systems have been developed to enable systematic assessment as well as to avoid unnecessary medical interventions and malignant findings being overlooked. This article provides an overview of the current diagnostic standards in primary assessment of thyroid nodules.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Calcitonin; Cytology; Diagnostic imaging; Fine needle aspiration; Thyroid neoplasms